Core–shell MoS2@graphene composite microspheres as stable anodes for Li-ion batteries. (23rd August 2018) - Xue, Haoliang; Wang, Jie; Wang, Shanshan; Muhammad, Sohail; Feng, Caihong; Wu, Qin; Li, Hansheng; Shi, Daxin; Jiao, Qingze; Zhao, Yun
Abstract : High-capacity lithium-ion battery anode materials of transition metal dichalcogenides often suffer from large volume expansion during lithiation, which causes capacity decay. Abstract : High-capacity lithium-ion battery anode materials of transition metal dichalcogenides often suffer from large volume expansion during lithiation, which causes capacity decay. Introducing a carbon material shell to limit their volume change is an effective way to prolong the cycling stability. Herein, MoS2 @graphene composite microspheres with core–shell architectures were synthesized by a novel and cost-effective method. Moreover, the MoS2 @graphene composite microspheres exhibit exceptional performance for Li storage. A high reversible capacity of ≈810 mA h g −1 is obtained at 100 mA h −1, which is maintained at 894 mA h g −1 after 100 cycles. Therefore, this work provides an effective approach to limit the volume expansion problem, which can be generally applied to other anode materials to improve their performance in LIBs.